Technical Competencies Required by Accountants: An Analysis of Accounting Job Advertisements - Rohmah, Mazidatur; Laily, Nujmatul (Universitas Negeri Malang, 2023)
The changing of business environment raises the question about the priority skills that are needed by the labour market in Indonesia. This study focuses on technical competencies in accounting education by exploring the company's point of view. This study aims to determine the technical competencies needed by accountants through analysis of accounting job advertisements. This study uses content analysis on 612 online job vacancies. The data was then tested differently using the non-parametric Kruskal Wallis test. The findings of this study indicated that information technology and financial reporting skills are the most needed technical competencies by companies. Specifically, the skills that should be mastered by accountants are the skills to use Microsoft office packages and prepare company financial reports. In addition, this study found that there are differences in the need for accounting technical competencies in each job position. The results of this study are expected to provide insight and self-reflection to accounting graduates regarding the technical competencies needed to enter the world of work, so that accounting graduates can fit themselves with the required skills so that they can easily be accepted in the desired job.